Makna Simbolik Bulang dan Gotong Pada Etnis Simalungun - Salsa Ovellia Putri; Maya Rifqi Nasution; Ewi Tania Apsela (Jurnal Indonesia Sosial Teknologi, 2022)
Indonesia is a developing country that has a myriad of different customs, social traditions and ancestors. North Sumatra is one area that should be used as a vacation spot, ranging from ordinary tourist attractions that have a beautiful appearance, culinary tours to tourist visits that have various destinations scattered throughout the North Sumatra region. One of them is the number of tourists visiting the Simalungun area because the Simalungun Batak community has a myriad of social qualities, customs, strict ceremonies, expressions, traditional house building designs, conventional goods, and conventional clothing, one of which is customs. material called Hiou or in English. Simalungun Batak are often referred to as Bulang and Gotong This research uses a qualitative descriptive method. According to Sugiono, qualitative research is research that places the researcher as the key instrument, data collection techniques are carried out in combination and data analysis is inductive. The results obtained As explained above that gotong partongah can only be worn by the king, while gotongparuma is used by the royal apparatus, but does not wear accessories in the form of rudang hapias, doramani, rantei gotong and tiger fangs. However, due to the transformation of clothing in Simalungun and the incident on March 3, 1946 in the form of the Social Revolution which destroyed various structures of the Simalungun society in the form of the disappearance of the Bolon house, the killing of the royal family, the robbery of noble property, as well as the waning of Simalungun's authority, as well as the loss of generations of educated people in Simalungun.